al-Lām al-Mufradah bayna Ittihādil-Māddah wa Ta'dādil-Wadzīfah - Muhammad Sayyed Hagag (University of Darussalam Gontor, 2017)
AbstractThis research focuses on Arabic letters which plays an important role in speech, its circulation and common use, its special vocal nature, its different pronunciation method, and multiple functions in speech. The letter is called Lam. This research is also devoted to the unity of material in the description of the Lam letter phonetically, and enumeration of the function of agent Lam such as: agent Lam for preposition, for affirmative, or for nominative. The methodology covers the enumeration of the function of non-agent Lam in its different types and functions. The Lam letter in speech such as word from Allah swt as mentioned in Surah Al-Kahf will be a model for those applications for its great advantage. It also covers displaying the statistics for the Lam letter used in that Surah al-Kahf while analyzing several models from the verses of Surah. In the end, the research showed that the most signicant results is that the Lam agent has multiple functions under three elements in speech which are: agent Lam for preposition, agent Lam for affirmative, or agent Lam for nominative, and the non-agent of Lam has many functions as well such as: Lam for oath speech form, Lam for initial, and Lam for assignment, and so on.Keywords: The letter of Lam, the union of material, differences of function, agent, non-agent.اللامُ الْمُفْرَدَةُ بَيْنَ اتِّحَادِ الْمَادَّةِ وَتَعْدَادِ الْوَظِيفَةِبقلم: محمد سيد حجاججامعة القاهرة الملخصيختص هذا البحث في حرف من الحروف العربية، له أهميته العظمى في الكلام، كثير الدوران، شائع الاستعمال والاستخدام، حرف ذو طبيعة صوتية خاصة، وطريق نطق مختلفة، ووظائف متعددة، فهو حرف واحد، متعدد الوظائف، إنه حرف اللام. وتخصص هذا البحث على اتحاد المادة، في وصف حرف اللام صوتيا، و تعداد الوظيفة عن اللام العاملة وهي في اللام العاملة للجر، وفي العاملة للجزم، وفي العاملة للنصب، و اللام غير العاملة بأنواعها ووظائفها المختلفة. اللام في الكلام من كلام الله فى سورة الكهف تكون نموذجا لهذا التطبيق؛ وذلك لفضلها العظيم، ثم عرض الإحصاء لحرف اللام فيها، و تحليل لبعض النماذج من آيات السورة، ثم عرض الباحث أن فيه أبرز النتائج و هي: اللام العاملة في الكلام لها وظائف متعددة تحت عناصر ثلاثة: العاملة للجر، والعاملة للجزم، والعاملة للنصب، واللام غير العاملة لها وظائف عديدة، منها: لام القسم، لام الابتداء، لام التعريف وغيرها.الكلمة الرئيسية: حرف اللام، اتحاد المادة، تعداد الوظيفة، العاملة، غير العاملة.